The unbearable heaviness of being: Analyzing Bigger Thomas from Richard Wright’s Native Son as a character beyond good and evil - Akter, Arfin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.